Characterization of the gut microbiota and fecal and blood metabolomes under various factors in urban children from Northwest China - Yang, Yan; Chen, Juanjuan; Gao, Huiyu; Cui, Minglu; Zhu, Mingyu; Xiang, Xuesong; Wang, Qi (Frontiers in Cellular and Infection Microbiology, 2024)
Children have regional dynamics in the gut microbiota development trajectory. Hitherto, the features and influencing factors of the gut microbiota, fecal and plasma metabolites in children from Northwest China remain unclear. Therefore, shotgun metagenomic sequencing and untargeted metabolomics were performed on 100 healthy volunteers aged 2-12 years. Age, body mass index (BMI), regular physical exercise (RPE) and delivery mode (DM) significantly affect gut microbiota and metabolites. Lactobacillus, Butyricimonas, Prevotella, Alistipes, and predicted pathway propanoate production were significantly increased with age while Bifidobacterium breve, B. animalis, B. pseudocatenulatum, Streptococcus infantis, and carbohydrates degradation were decreased. Fecal metabolome revealed that metabolism of caffeine, amino acids, and lipid significantly increased with age while galactose metabolism decreased. Noticeably, BMI was positively associated with pathogens including Erysipelatoclostridium ramosum, Parabacteroides distasonis, Ruminococcus gnavus, and amino acids metabolism but negatively associated with beneficial Akkermansia muciniphila, Alistipes finegoldii, Eubacterium ramulus, and caffeine metabolism. RPE has increased probiotic Faecalibacterium prausnitzii and Anaerostipes hadrus, acetate and lactate production, major nutrients metabolism in gut and plasma, but decreased pathobiont Bilophila wadsworthia, taurine degradation, pentose phosphate pathway. Interestingly, DM affect the gut microbiota and metabolites throughout the whole childhood. Bifidobacterium animalis, Lactobacillus mucosae, L. ruminis, primary bile acid and neomycin biosynthesis were enriched in eutocia, while anti-inflammatory Anaerofustis stercorihominis, Agathobaculum butyriciproducens, Collinsella intestinalis, and pathgenic Streptococcus salivarius, Catabacter hongkongensis, and amino acid metabolism were enriched in Caesarean section children. Our results provided theroretical and data foundation for the gut microbiota and metabolites in preadolescent children's growth and development in Northwest China.Importance: The gut microbiota in preadolescence is important for long-term growth and development of individuals. Hitherto, the characteristics and influencing factors of the gut microbiota, fecal and plasma metabolites in children from Northwest China remain unclear. Shotgun metagenomic sequencing and untargeted metabolomics were performed on 100 healthy volunteers aged 2-12 years. We have revealed that age, body mass index, regular physical exercise and delivery mode could affect the gut microbiota and metabolites. Our study will expand the Chinese database of the gut microbiota and metabolites, and provide theroretical and data foundation for the gut microbiota in health care in preadolescent children.